Strategies mitigating hypoxaemia in high-risk populations during anaesthesia and respiratory critical care: computational modelling studies - Alahmadi, Husam I. (2021)
Assessing interventions applied during clinically-encounterable extreme scenarios is vital to enhance the quality of care. However, the studies that examine these situations are rare, ethically and clinically challenging. Computational modelling offers a reliable, efficient and almost ethical-free approach to investigate high-risk scenarios. This thesis evaluated interventions applied during (i) prolonged apnoea in obesity, (ii) airway obstruction in emergency crises, and (iii) hyperbaric oxygen therapy in severe hypoxaemic respiratory failure patients through a series of high-fidelity computational modelling studies.